Destruction of the Northern Margin of the North China Craton in Mid‐Late Triassic: Evidence from Asthenosphere‐derived Mafic Enclaves in the Jiefangyingzi Granitic Pluton from the Chifeng Area, Southern Inner Mongolia. (30th August 2020) - LIU, Jianfeng; LI, Jinyi; CHI, Xiaoguo; ZHENG, Peixi; HU, Zhaochu; ZHANG, Xiaowei
Abstract : Abstract: The petrology, geochronology and geochemistry of the mafic enclaves in the Mid‐Late Triassic Jiefangyingzi pluton from Chifeng area, southern Inner Mongolia, in China are studied to reveal their petrogenetic relationship with the host pluton. Furthermore, the coeval magmatic assemblage and its petrogenesis on the northern margin of the North China craton (NCC) are studied synthetically to elucidate their tectonic setting and the implications for the destruction of the NCC. Zircon U‐Pb dating reveals that the mafic enclaves formed at 230.4 ± 2.2 Ma, which is similar to the age of the host pluton. The most basic mafic enclaves belong to weak alkaline rocks, and they display rare earth element (REE) and trace element normalized patterns and trace element compositions similar to those of ocean island basalt (OIB). In addition, they have positive ∊ Nd ( t ) values (+3.84 to +4.94) similar to those of the Cenozoic basalts on the northern margin of the NCC. All of these geochemical characteristics suggest that the basic mafic rocks originated from the asthenosphere. Petrological and geochemical studies suggest that the Jiefangyingzi pluton and the intermediate mafic enclaves were formed by the mixing of the asthenosphere‐derived and crust‐derived magmas in different degrees. The Mid‐Late Triassic magmatic rocks on the northern margin of the NCC could be classified into three assemblages according to their geochemical compositions: alkaline series, weak alkaline–sub‐alkaline series and sub‐alkaline series rocks. Petrogenetic analyses suggest that the upwelling of the asthenosphere played an important role in the formation of these Mid‐Late Triassic magmatic rocks. Basing on an analysis of regional geological data, we suggest that the northern margin of the NCC underwent destruction due to the upwelling of the asthenosphere during the Mid‐Late Triassic, which was induced by the delamination of the root of the collisional orogeny between Sino‐Korean and Siberian paleoplates in Late Permian.